Performance Estimation of Scheduling Algorithms on Microblaze Softcore Processor - Das, Manisha; Admane, SV; Zalke, Jitendra B (International Journal of Computer Sciences and Engineering, 2025)
Multitasking or multiprocessing is the need of today’s modern embedded system. Multitasking can reach the desired increase in performance as needed by today’s embedded systems. Multitasking can be achieved by scheduling the competing tasks and allocate them to the shared resources one by one at very high speed (so fast and frequently) so as to create an illusion that all tasks are running in parallel. There are various algorithms to implement a scheduling scheme depending upon the need and constraints of the application. The proposed research work aims at evaluating and comparing the performance of Round Robin and Static Priority Scheduling algorithm by implementing them the on single Microblaze soft core processor and porting xilkernel on FPGA platform.